A Misoginia no YouTube Brasileiro: Um Estudo de Caso sobre o Conteúdo Produzido pela Comunidade Red Pill - Martins, Victor; Serafim, Sophia Eduarda V.; Pereira, Lívia Caroline R.; Alves, Amanda F.; Ferreira, Carlos H. G.; Almeida, Jussara M. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2025)
YouTube, as one of the most influential video platforms in Brazil, has become a central space for the circulation of ideas and, consequently, a fertile ground for the spread of hate speech, particularly misogyny, within the Manosphere ecosystem. The growing visibility and influence of content creators highlight the urgency of understanding how their messages are constructed and received. While previous studies have examined online misogyny in other platforms and contexts, little is known about its large-scale manifestations in the Brazilian YouTube ecosystem, especially regarding the practices of particular communities. This study addresses this gap by examining the presence and activity of the Red Pill community on YouTube Brazil, aiming to characterize how misogynistic discourse is constructed, interpreted, and propagated. We analyzed 18,034 videos and over 2.2 million comments from 28 channels published between January 2024 and June 2025, applying state-of-the-art natural language processing techniques to investigate engagement patterns and discursive dynamics. Our findings reveal that this community reaches a wide audience through diverse content strategies shaped by creators themselves. While titles and descriptions predominantly convey neutral sentiment, possibly to maximize reach and avoid automated moderation, user comments display a pronounced prevalence of negative sentiment and elevated toxicity. These results underscore the role of content creators in exploring YouTube to amplify extremist narratives and contribute to the understanding of online misogyny in Brazil by shedding light on its mechanisms of construction, reception, and dissemination.